Incorporating low-cycle fatigue model into duration-dependent inelastic design spectra. - Chai, Y.H.
Seismic performance of structures is related to the damage inflicted on the structure by the earthquake, which means that formulation of performance based design is inherently coupled with damage assessment of the structure. Although the potential for cumulative damage during a long duration earthquake is generally recognized, most design codes do not explicitly take into account the damage potential of such events. In this paper, the classical low cycle fatigue model commonly used for seismic damage assessment is cast in a framework suitable for incorporating cumulative damage into seismic design. The model, in conjunction with a seismic input energy spectrum, may be used to establish an energy based seismic design. In order to ensure satisfactory performance in a structure, the cyclic plastic strain energy capacity of the structure is designed to be larger than or equal to the portion of seismic input energy contributing to cumulative damage. The resulting design spectrum, which depends on the duration of the ground motion, indicates that the lateral strength of the structure must be increased in order to compensate for the increased damage due to an increased number of inelastic cycles that occur in a long duration ground motion. Examples of duration-dependent inelastic design spectra are developed using parameters currently available for the low cycle fatigue model. The resulting spectra are also compared with spectra developed using a different cumulative damage model.
Keywords: Cumulative damage; Ground motion duration; Seismic design spectra; Input energy